Analisis Sistem Gerak yang Memengaruhi Keseimbangan Tubuh Lansia - Gea, Fifitriani; Hulu, Adil Hati; Lase, Natalia Kristiani (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The elderly are prone to experiencing body balance disorders that can result in falls. This is influenced by various factors, including the movement system that changes with age. The researcher's goal is to analyze the movement system that affects the balance of the body of the elderly. The researcher used the literature review method by looking for data from scientific journals. The main source of data for this research is obtained through academic search engines, such as google scholar. Data analysis is carried out qualitatively consisting of data reduction, data presentation, and conclusion drawing. Based on the results obtained from the movement system that affects the balance of the elderly body includes, the musculoskeletal system where the decrease in muscle strength and mass, joint stiffness, and osteoporosis can interfere with balance, the second is the nervous system, where the decline in the function of the central and peripheral nervous system can interfere with coordination and reflexes needed to maintain balance, and finally the vestibular system located in the inner ear which can interfere with perception Balance. Decreased motor system function in the elderly can affect body balance and increase the risk of falls. Two parties that target the elderly's mobility system, such as physical exercise and rehabilitation therapy, can help improve balance and reduce the risk of falls